Exosomes from NSC-34 Cells Transfected with hSOD1-G93A Are Enriched in miR-124 and Drive Alterations in Microglia Phenotype - Pinto, Sara; Cunha, Carolina; Barbosa, Marta; Vaz, Ana R.; Brites, Dora (Frontiers in Neuroscience, 2017)
Amyotrophic lateral sclerosis (ALS) is a fatal adult-onset neurodegenerative disorder affecting motor neurons (MNs). Evidences indicate that ALS is a non-cell autonomous disease in which glial cells participate in both disease onset and progression. Exosomal transfer of mutant copper-zinc superoxide dismutase 1 (mSOD1) from cell-to-cell was suggested to contribute to disease dissemination. Data from our group and others showed that exosomes from activated cells contain inflammatory-related microRNAs (inflamma-miRNAs) that recapitulate the donor cell. While glia-derived exosomes and their effects in neurons have been addressed by several studies, only a few investigated the influence of motor neuron (MN)-derived exosomes in other cell function, the aim of the present study. We assessed a set of inflamma-miRs in NSC-34 MN-like cells transfected with mutant SOD1(G93A) and extended the study into their derived exosomes (mSOD1 exosomes). Then, the effects produced by mSOD1 exosomes in the activation and polarization of the recipient N9 microglial cells were investigated. Exosomes in coculture with N9 microglia and NSC-34 cells [either transfected with either wild-type (wt) human SOD1 or mutant SOD1(G93A)] showed to be transferred into N9 cells. Increased miR-124 expression was found in mSOD1 NSC-34 cells and in their derived exosomes. Incubation of mSOD1 exosomes with N9 cells determined a sustained 50% reduction in the cell phagocytic ability. It also caused a persistent NF-kB activation and an acute generation of NO, MMP-2, and MMP-9 activation, as well as upregulation of IL-1β, TNF-α, MHC-II, and iNOS gene expression, suggestive of induced M1 polarization. Marked elevation of IL-10, Arginase 1, TREM2, RAGE, and TLR4 mRNA levels, together with increased miR-124, miR-146a, and miR-155, at 24 h incubation, suggest the switch to mixed M1 and M2 subpopulations in the exosome-treated N9 microglial cells. Exosomes from mSOD1 NSC-34 MNs also enhanced the number of senescent-like positive N9 cells. Data suggest that miR-124 is translocated from the mSOD1 MNs to exosomes, which determine early and late phenotypic alterations in the recipient N9-microglial cells. In conclusion, modulation of the inflammatory-associated miR-124, in mSOD1 NSC-34 MNs, with potential benefits in the cargo of their exosomes may reveal a promising therapeutic strategy in halting microglia activation and associated effects in MN degeneration.